Design of triple-band h slot patch antenna - Noori, Omar; Chebil, Jalel; Sheroz Khan, Sheroz Khan; Islam, Md. Rafiqul (2011)
This paper attempts to design a triple band h-slot antenna by using feed line technique. These bands cover GSM mobile phone system (0.9 and 1.8 GHz) and ISM band which is used for Bluetooth and wireless local area network bands applications. The CST microwave studio software is used as a tool for simulation. This antenna is an attractive candidate for important applications like mobile phone communication systems, mobile phone jammer application, and so on.